The Risk Factors and Outcome of Acute Kidney Injury in the Intensive Care Units - Park, Woo Young (The Korean Association of Internal Medicine, 2010)
BACKGROUND/AIMS: Acute kidney injury (AKI) is a common and serious complication in critically ill patients, especially in the intensive care unit (ICU). The present study was performed to evaluate the occurrence rate of AKI using the RIFLE (increasing severity classes risk, injury, and failure, and the two outcome classes loss and end-stage kidney disease) classification, to define factors associated with AKI and hospital mortality. METHODS: We performed a retrospective study of all ICU patients over a 6-month period at Keimyung University Dongsan Hospital, Daegu, Korea. AKI was evaluated according to the RIFLE classification. RESULTS: AKI occurred in 156 of the 378 patients (41.3%) during their ICU stay, with maximum RIFLE-R, I, and F in 13.8%, 12.4%, and 15.1%, respectively. In univariate analysis, the proportion of medical admission and maximum Sequential Organ Failure Assessment (SOFA) score (SOFAmax) were significantly higher in patients with AKI than in those without. However, these factors did not remain significant in a multivariate analysis. The overall mortality rate of ICU patients was 25.7%. In multivariate analysis, mean age, occurrence of AKI, SOFAmax score, pulmonary disease, and malignancy were independent risk factors for hospital mortality. CONCLUSIONS: In these ICU patients, AKI is associated with increased hospital mortality. The RIFLE classification is a simple and useful clinical tool to detect and stratify the severity of AKI, and may aid in the prediction of outcome.